Evolução para hipotireoidismo congênito permanente e transitório no Programa de Triagem Neonatal em Sergipe - Matos, Diana Melo de (2015)
Objectives: The introduction of neonatal screening programs (NSP) led to an increased in detection of congenital hypothyroidism (CH). This increase may be due to ethnic composition (predominance of Iberian and Asian people), environmental factors (temperature and iodine intake) and inclusion of cases of transient CH and hyperthyrotropinemia, defined by moderate elevation of TSH with normal T4. The main objectives of this study were to evaluate, in children with altered neonatal screening tests in the NSP in the Northeastern Brazilian Sergipe state, the evolution for permanent or temporary condition and to evaluate the mean incidence of permanent CH, hyperthyrotropinemia and transient TSH elevation. Subjects and methods: Review of medical records of children with altered neonatal and confirmatory TSH from 2004 to 2010 (levels more than 5.2 μU/ml and 4.2 μU/ml, respectively), followed at the Clinic of Pediatric Endocrinology of the University Hospital of the Federal University of Sergipe. From the confirmatory serum TSH values, children were classified as initial CH: serum TSH > 10.0 μU/ml; or suspect CH: serum TSH > 4.2 μU/ml and ≤ 10.0 μU/ml. According to follow-up parameters, the final diagnosis included three categories. Permanent CH: Serum TSH > 10.0 μU/ml, independent of T4 levels or current use of thyroxine; or without l-thyroxine use serum TSH level between 4.2 μU/ml and 10.0 μU/ml, but with low free T4 or total T4. Hyperthyrotropinemia: children without l-thyroxine use with serum TSH level between 4.2 μU/ml and 10.0 μU/ml with normal free T4 and total T4. Transient TSH elevation: Initial CH or suspect CH children which normalized in the follow up without l-thyroxine treatment (serum TSH ≤ 4.2 μU/ml, free T4 ≥ 0.79 ng/dl and total T4 ≥ 7.2 μg/dl). The mean incidence of permanent CH, hyperthyrotropinemia and transient TSH elevation in the period was calculated by dividing the number of children with each category for the total number of children screened. Results: The initial diagnosis included 37 cases of initial CH (18.1%) and 167 suspect CH (81.9%). The final diagnosis included 46 cases of permanent CH (22.5%); 56 hyperthyrotropinemia (27.5%) and 102 transient TSH elevation (50.0%). Out of the 37 cases of initial CH, it was found 23 (62.2%) of permanent CH; 9 (24.3%) of hyperthyrotropinemia; and 5 (13.5%) of transient TSH elevation. Out of the 167 suspects, it was found 23 (13.8%) of permanent CH, 47 (28.1%) of hyperthyrotropinemia and 97 (58.1%) of transient TSH elevation. We found a mean incidence of 1:4166 of permanent CH, 1:3448 of hyperthyrotropinemia and 1:1887 of transient TSH elevation. 86.5% of children with an initial diagnosis of CH and 41.9% of suspicions have permanent condition (CH or hyperthyrotropinemia). Conclusions: The follow-up of children with initial diagnosis and suspicion is necessary to characterize the permanence or not of the disorder, since the prediction of the evolution of children with initial CH or suspect is difficult.